Uses of the Science textbook in a countryside school - Raimunda Alves Melo; Antonia Pereira de Macedo (Universidade Federal do Norte do Tocantins, 2020)
The general objective of this study is to understand the use of the Didactic Book (LD) of Natural Sciences in classes from 6th to 9th year of rural schools. Specifically, the research aimed to know the methodological uses of the Natural Sciences LD in classes from the 6th to the 9th year of elementary school in rural schools and to identify how teachers use the LD of Natural Sciences. Descriptive research was carried out, with a qualitative approach, since this type of research was the one best suited to the object and objectives of the study. Data collection instruments, simple observation and interview were used as instruments. The study was carried out in one of the rural located in the municipality of Juazeiro do Piauí. The interlocutors were two teachers who works with the curricular component of Natural Sciences and who joined the research in a free and conscious way. The results point out that methodological tensions in the use of the Natural Sciences LD, include failures in the selection process and the availability by the Ministry of Education (MEC) of materials that do not value peasant reality. Thus, it is necessary to implement continuous training processes through which teachers reflect on their conceptions of rural and peasant culture and dynamize the ways of using LDs.